Viral Dynamics of Omicron and Delta Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Variants With Implications for Timing of Release from Isolation: A Longitudinal Cohort Study. (2nd August 2022) - Bouton, Tara C; Atarere, Joseph; Turcinovic, Jacquelyn; Seitz, Scott; Sher-Jan, Cole; Gilbert, Madison; White, Laura; Zhou, Zhenwei; Hossain, Mohammad M; Overbeck, Victoria; Doucette-Stamm, Lynn; Platt, Judy; et al.
Abstract: Background: In January 2022, US guidelines shifted to recommend isolation for 5 days from symptom onset, followed by 5 days of mask-wearing. However, viral dynamics and variant and vaccination impact on culture conversion are largely unknown. Methods: We conducted a longitudinal study on a university campus, collecting daily anterior nasal swabs for at least 10 days for reverse-transcription polymerase chain reaction (RT-PCR) testing and culture, with antigen rapid diagnostic testing (RDT) on a subset. We compared culture positivity beyond day 5, time to culture conversion, and cycle threshold trend when calculated from diagnostic test, from symptom onset, by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant, and by vaccination status. We evaluated sensitivity and specificity of RDT on days 4–6 compared with culture. Results: Among 92 SARS-CoV-2 RT-PCR–positive participants, all completed the initial vaccine series; 17 (18.5%) were infected with Delta and 75 (81.5%) with Omicron. Seventeen percent of participants had positive cultures beyond day 5 from symptom onset, with the latest on day 12. There was no difference in time to culture conversion by variant or vaccination status. For 14 substudy participants, sensitivity and specificity of day 4–6 RDT were 100% and 86%, respectively. Conclusions: The majority of our Delta- and Omicron-infected cohort culture-converted by day 6, with no further impact of booster vaccination on sterilization or cycle threshold decay. We found that rapid antigen testing may provide reassurance of lack of infectiousness, though guidance to mask for days 6–10 is supported by our finding that 17% of participants remained culture-positive after isolation. Abstract : Cabotegravir+rilpivirine long-acting dosed every 8 weeks continued to be noninferior to every-4-week dosing over 152 weeks, with comparable safety profiles and no new safety signals since week 96. These data demonstrate durability of virologic suppression with cabotegravir+rilpivirine long-acting for nearly 3 years.